1986
DOI: 10.1007/bf01870809
|View full text |Cite
|
Sign up to set email alerts
|

A Ca-dependent K channel in “luminal” membranes from the renal outer medulla

Abstract: This paper describes properties of 86Rb fluxes through K channels in "luminal" membrane vesicles prepared from rabbit renal outer medulla. By measuring 86Rb uptake against an opposing chemical gradient of K ions, using membranes loaded with KCl, a transient accumulation of isotope is observed, which is blocked by Ba ions. This is the behavior expected of a conductive Rb flux through a Ba-sensitive K channel. The 86Rb accumulation is driven by an electrical diffusion potential as shown in experiments using eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…2 show that approximately 40% of the total S6Rb+ uptake was inhibited by 2 mM BaCI2. This relatively prolonged uptake phase is consistent with the results of Burnham et al [3] and is typical of conductive K § transport when measured under these conditions…”
Section: Na+ Uptake Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…2 show that approximately 40% of the total S6Rb+ uptake was inhibited by 2 mM BaCI2. This relatively prolonged uptake phase is consistent with the results of Burnham et al [3] and is typical of conductive K § transport when measured under these conditions…”
Section: Na+ Uptake Studiessupporting
confidence: 86%
“…The conditions for ~'Rb + uptake were similar to those described by Burnham et al [3]. Specifically, we assayed Ba2+-sensitive ~Rb + uptake, which was ouabain-and bumetanide-insensitive in vesicles loaded, as described above, with I mM ATP.…”
Section: Procedures For Measuring S6rb+ Uptakementioning
confidence: 99%
“…The membrane vesicle preparation used in this study has been previously shown to be highly enriched in the basolateral marker Na+/K + ATPase (Jorgensen, 1974), as well as luminal TALH markers such as the Na~/K+/2C1 cotransporter and K + channel (Burnham et al, 1985;Burnham, Braw & Karlish, 1986;Klaerke et al, 1987). Analysis by sodium dodecyl sulfate polyacrylamide gel electrophoresis showed that the 95 kilodalton c~-chain of the Na+/K + ATPase was by far the predominant protein band in the membrane preparation (not shown).…”
Section: Discussionmentioning
confidence: 91%
“…Wiener et al: Ca2+-Activated K* Channels mM MOPS-Tris, pH 7.2, at 20~ Furosemide (1 raM) was added to increase the sensitivity of the flux measurements by blocking the Na,K,Cl-cotransport system present in the colon epithelium [42]. In experiments where stimulatory effects of Ca 2+ were investigated, vesicles were preincubated for 30 rain in 3.75 mM EGTA and l0/~M CaX+-ionophore A23187 in order to deplete the vesicles of endogenous Ca 2+ [5,23]. The presence ofA23187 in the membrane ensures that the activities of Ca 2+ are the same inside and outside the membrane vesicles irrespective of their orientation.…”
Section: Reconstitution Of K + Channel Activitymentioning
confidence: 99%